2000
DOI: 10.1093/carcin/21.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effect of 24R,25-dihydroxyvitamin D3 in N,N'-dimethylhydrazine-induced rat colon carcinogenesis

Abstract: In this study we investigated the effects of 24R,25-dihydroxyvitamin D(3) [24R,25(OH)(2)D(3)] on N,N'-dimethylhydrazine (DMH)-induced rat colon carcinogenesis. For experiments 1 and 2, 50 F344 male, 6-week-old rats were divided into five groups in each experiment. Animals were given s.c. injections of DMH once a week for 4 weeks. Those in groups 1-5 were given 24R,25(OH)(2)D(3) in the diet (10, 5, 2.5, 1.25 or 0 p.p.m., respectively) during the post-initiation stage in experiment 1 and during the initiation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Moreover, both serum levels of vitamin D 3 at the high end of the physiological range 21,22 and consumption of polyphenol-rich diets are consistent with lower risk of certain cancers. 32,33 This is supported by the findings that both VDDs [67][68][69] and rosemary extract and its purified components [56][57][58] suppressed experimental carcinogenesis. Thus, it seems plausible to hypothesize that these compounds may also cooperate in their chemopreventive action.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, both serum levels of vitamin D 3 at the high end of the physiological range 21,22 and consumption of polyphenol-rich diets are consistent with lower risk of certain cancers. 32,33 This is supported by the findings that both VDDs [67][68][69] and rosemary extract and its purified components [56][57][58] suppressed experimental carcinogenesis. Thus, it seems plausible to hypothesize that these compounds may also cooperate in their chemopreventive action.…”
Section: Discussionmentioning
confidence: 70%
“…Experimental studies suggest that vitamin D may inhibit cell proliferation (Shabahang et al, 1994;Cross et al, 1992;Wallach et al, 1966;Taniyama et al, 2000). The cell growth inhibitory properties of the vitamin appear to be related to the concentrations of vitamin D receptors on the cell surface rather than vitamin D concentrations.…”
Section: Vitamin Dmentioning
confidence: 99%
“…The reason for the discrepancy with the many previous studies which showed chemopreventive effects on colon carcinogenesis and ACF development [1][2][3][4]27,31,32 , may be due to the different number of treatment times per week. DHA was injected five times a 20,21,23,33 incidences of colon tumor development have been reported to range from 10 to 80%, therefore the figure of 10% achieved in the present study was relatively low. Thus, one reason for the lack of obvious influence of DHA could have been due to weak initiation.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, we thought it important to investigate the difference in the modifying effects on carcinogenesis of DHA-E and DHA-TG. In the present study, we investigated the post-initiation-phase modifying activity of DHA-E and DHA-TG at the whole organ level using a rat medium-term multi-organ carcinogenesis model developed in our laboratory 8,15,19,20 . Furthermore, a tocopherol group was included as a comparative control.…”
Section: Introductionmentioning
confidence: 99%